Causality between VAT and economic growth in Nigeria: An ARDL bounds testing approach / Hammed Agboola Yusuf … [et al.] - Yusuf, Hammed Agboola; Zainal Abidin, Irwan Shah; Bakar, Normiza; Musibau, Oluwaseyi Hammed (Universiti Teknologi MARA Selangor, 2018)
Value Added Tax(VAT) is a consumption tax imposed at every stage of consumption level whose burden is burned by final consumer of goods and services. In most developing economies in the world, VAT as a source of revenue to the government that has been notable for its significant role in ensuring economic efficiency. However, VAT revenue has been underutilised in Nigeria due to a high level of corruption in the process of administering the tax. This study examines the impact of VAT, domestic investment and trade openness on economic growth in Nigeria from 1980 to 2016 using ARDL techniques. The research design is time series, and the data were analysed using time series unit root test, error correction model regression, short run and long run ARDL. The result found that VAT, domestic investment and trade openness had a positive and significant impact on real GDP. Also, corruption index is negative also significant in the long run. In the same vein, past value added tax had a negative and weak significant impact on real gross domestic product indicating convergence to long-run causality between economic growths and VAT and economic growth. The Error Correction Model (ECM (-1)) coefficient had a negative and statistically significant sign. This shows that 39 percent can quickly correct short-run deviation. The study, therefore, recommends that tax administrative loopholes should be plugged for tax revenue to contribute immensely to the development of the economy since past VAT had a significant impact on economic growth.